EDITORIAL: REFLECTIONS ON MEN, MASCULINITIES AND MEANING IN SOUTH AFRICA - Shefer, Tamara; Bowman, Brett; Duncan, Norman (PINS-Psychology in Society, 2025)
The articles contained in this special issue were first presented at a doctoral symposium held at the University of the Witwatersrand in August 2007. Both this special issue and the symposium on which it is based represent in some ways intersecting responses to at least three concerns. The first unsurprisingly resided in the need to contribute to and perhaps extend the seminal work on masculinities that is currently being undertaken in South Africa. The second and in some ways more powerful motivation related to what seemed to be a rapid succession of harrowing media reports of violence involving men and boys at the time. In February 2007, three boys were stabbed during a fight at a secondary school in Pretoria. In the space of a single week in late May 2007, there were as many as three different violent attacks (two of them fatal, with one of the victims only 8 years old) on school learners by their classmates in the Western Cape. In the same week, an adolescent boy was murdered, allegedly over a cell phone at a secondary school in KwaZulu Natal. News reports of similar events continued without respite in 2008. For example, in August 2008 the South African public was shocked by a brutal attack by an 18-year old boy at a Krugersdorp school who slashed open the neck of a 16-year-old learner with a Samurai-style sword and proceeded to wound a number of others on the school premises.